Application of E-Commerce in Improving UMKM Economic - Tatiek Setyorini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to analyze the application of e-commerce, strategies for using e-commerce and the impact of using e-commerce in improving the economy of UMKMs in Tisnonegaran Village, Probolinggo City. The method in this research uses a qualitative analysis method with a field research model. Data collection methods use interviews, observation and documentation. The results of this research are 1) The application of E-commerce in improving the economy of UMKMs in Tisnonegaran Village, Probolinggo City, which plays an important role in empowering and improving the quality of the community's economy through technological support. E-commerce provides services that are concise, effective and efficient so that they can be done anywhere and at any time and can increase revenue turnover. 2) The strategy for using E-Commerce in improving the UMKM economy in Tisnonegaran Village, Probolinggo City, namely improving the quality of human resources, good and fast service strategies, providing the best prices and discounts to attract customer interest and displaying descriptions of goods according to conditions and providing attractive photos. . 3) The use of e-commerce will have positive impacts such as increasing income, products being easily recognized by consumers, saving promotional costs, increasing the speed of transactions that can be accessed 24 times and providing security and convenience in the transaction process. Apart from having a positive impact, the use of e-commerce also has a negative impact, such as increasingly fierce competition.